2020
DOI: 10.1186/s12879-020-04974-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of nucleic acid tests in tuberculous pleurisy

Abstract: Background: Tuberculous pleurisy (TBP) is the most common form of extrapulmonary tuberculosis (TB). However, rapid diagnostic methods with high accuracy for tuberculous pleurisy are urgently needed. In the present study, we evaluated the diagnostic accuracy of Xpert MTB/RIF, LAMP and SAT-TB assay with pleural fluids from culture-positive TBP patients. Methods:We prospectively enrolled 300 patients with exudative pleural effusions used as the samples for Xpert MTB/RIF, LAMP and SAT-TB assay. Of these, 265 inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(21 reference statements)
0
4
0
1
Order By: Relevance
“…A total of 27 out of the 30 included studies showed pooled sensitivity greater than 70%. Only three studies reported sensitivity values of 26% and 45% each ( 19 - 21 ). In terms of FP rate (1-specificity), 27 included studies showed a pooled FP rate higher than 80% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 27 out of the 30 included studies showed pooled sensitivity greater than 70%. Only three studies reported sensitivity values of 26% and 45% each ( 19 - 21 ). In terms of FP rate (1-specificity), 27 included studies showed a pooled FP rate higher than 80% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One (1.4%) study was conducted exclusively in HIV seropositive patients [ 43 ], while seven (9.5%) others included a variable number of such subjects [ 37 , 38 , 42 , 44 , 53 , 70 , 89 ]. There were no HIV seropositive patients in thirteen (17.6%) publications [ 30 , 47 , 63 , 73 , 74 , 76 , 78 , 79 , 83 , 84 , 88 , 92 , 96 ], while the remaining did not provide any information. Ten investigators thawed cryopreserved fluid samples for their tests [ 23 , 31 , 35 , 42 , 60 , 66 , 73 , 78 , 80 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 18 articles were included for meta‐analysis. 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 …”
Section: Resultsmentioning
confidence: 99%